2016
DOI: 10.1371/journal.pone.0154633
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Expression Pattern and Polymorphisms of NADPH-Cytochrome P450 Reductase in the Bird Cherry-Oat Aphid Rhopalosiphum padi (L.)

Abstract: NADPH–cytochrome P450 reductase (CPR) plays an important role in the cytochrome P450 (CYP)-mediated metabolism of endogenous and exogenous substrates. CPR has been found to be associated with insecticide metabolism and resistance in many insects. However, information regarding CPR in the bird cherry-oat aphid, Rhopalosiphum padi, is unavailable. In the current study, a full-length cDNA (2,476 bp) of CPR (RpCPR) encoding 681 amino acids was cloned from R. padi. Nucleotide sequence and deduced amino acid sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 64 publications
(83 reference statements)
0
24
0
Order By: Relevance
“…It was reported that a bioassay method that combined direct contact with an insecticide and subsequent exposure to residues on leaves gave a measurable resistance factor in the determination of resistance of M. persicae to neonicotinoids, while the resistance level could not be measured because of insufficient mortality at the highest concentration when using a bioassay method that applied the insecticide directly to the dorsal surface of individual aphids . We adopted a leaf‐dipping bioassay method that combined direct contact and residue exposure for the insects in this study . Stocks of insecticides were prepared in acetone (10 g L ‐1 ) and diluted in a series of concentrations containing 0.01% (v/v) Triton X‐100 for bioassays.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that a bioassay method that combined direct contact with an insecticide and subsequent exposure to residues on leaves gave a measurable resistance factor in the determination of resistance of M. persicae to neonicotinoids, while the resistance level could not be measured because of insufficient mortality at the highest concentration when using a bioassay method that applied the insecticide directly to the dorsal surface of individual aphids . We adopted a leaf‐dipping bioassay method that combined direct contact and residue exposure for the insects in this study . Stocks of insecticides were prepared in acetone (10 g L ‐1 ) and diluted in a series of concentrations containing 0.01% (v/v) Triton X‐100 for bioassays.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…9 We adopted a leaf-dipping bioassay method that combined direct contact and residue exposure for the insects in this study. 5 Stocks of insecticides were prepared in acetone (10 g L -1 ) and diluted in a series of concentrations containing 0.01% (v/v) Triton X-100 for bioassays. Wheat leaves with apterous adult aphids were dipped into insecticide solutions for 10 s, and the residual droplets of the solution on the leaves were absorbed by dry filter paper.…”
Section: Bioassaysmentioning
confidence: 99%
See 2 more Smart Citations
“…padi, insecticide-resistant samples from China have been recently described (Wang et al, 2016(Wang et al, , 2018. However, it remains unknown whether these strains correspond to clonal lineages developing as superclones.…”
Section: The Success Of Aphid Superclones and Challenges To Pest Manamentioning
confidence: 99%